Linear and quadratic convection significance on the dynamics of MHD Maxwell fluid subject to stretched surface - Akbar, Asia Ali; Awan, Aziz Ullah; Bani-Fwaz, Mutasem Z.; Tag-ElDin, ElSayed M.; Guedri, Kamel; Yassen, Mansour F.; Ali, Bagh (Frontiers in Physics, 2022)
The heat transmission process is a prominent issue in current technology. It occurs when there is a temperature variation between physical processes. It has several uses in advanced industry and engineering, including power generation and nuclear reactor cooling. This study addresses Maxwell fluid’s steady, two-dimensional boundary layer stream across a linearly stretched sheet. The primary objective of this research is to investigate the impact of the non-Newtonian fluid parameter (Deborah number) on flow behavior. The secondary objective is to investigate the effect of linear and quadratic convection to check which model gives higher heat transfer. The flow is caused by the surface stretching. The mathematical model containing the underlying partial differential equations (PDEs) is built using the boundary layer estimations. The governing boundary layer equations are modified to a set of nonlinear ordinary differential equations (ODEs) using similarity variables. The bvp4c approach is employed to tackle the transformed system mathematically. The impacts of numerous physical parameters like stretching coefficient, mixed convective parameter, heat source/sink coefficient, magnetic coefficient, variable thermal conductance, Prandtl number, and Deborah number over the dimensionless velocity and temperature curves are analyzed via graphs and calculated via tables. After confirming the similarity of the present findings with several earlier studies, a great symmetry is shown. The findings show that the linear convection model gains more heat transport rate than the quadratic convection model, ultimately giving a larger thermal boundary layer thickness. Some numeric impacts illustrate that boosting the magnetic coefficient elevates the fluid’s boundary layer motion, causing an opposite phenomenon of Lorentz force because the free stream velocity exceeds the stretched surface velocity.